DEVELOPING AUDIO-VISUAL TEACHING MEDIA FOR TEACHING MICROTEACHING SUBJECT FOR FOR S-1 STUDENTS OF ENGLISH EDUCATION DEPARTMENT LANGUAGE AND ART FACULTY GANESHA UNIVERSITY OF EDUCATION SINGARAJA - ., KOMANG RUSMA ARI SANTHI; ., PROF. DR. NI NYOMAN PADMADEWI, M.A.; ., DR. LUH PUTU ARTINI, M.A. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2016)
Penelitian ini bertujuan untuk: 1) mengidentifikasi jenis media pengajaran audio-visual yang dibutuhkan untuk pengajaran mata kuliah microteaching, 2) mengembangkan jenis media pengajaran audio-visual untuk pengajaran mata kuliah microteaching, 3) mengetahui kualitas jenis media pengajaran audio-visual untuk pengajaran mata kuliah microteaching untuk mahasiswa S-1 Program-studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Pendidikan Ganesha Singaraja. Penelitian ini menggunakan model R&D oleh Sugiyono (2010). Data dalam penelitian ini dikumpulkan dengan menggunakan dua alat: catatan dan kuesioner dan dianalisis dengan menggunakan analisis deskripsi kualitatif and kuantitatif. Hasil penelitian ini terungkap bahwa: pertama, dua jenis media pengajaran audio-visual dikembangkan untuk pengajaran mata-kuliah microteaching yaitu PowerPoint digunakan untuk mengajar konsep dan video digunakan untuk mengajar model pembelajaran, dua video dikembangkan yakni video pengajaran pada sekolah menengah pertama (SMP) dan pengajaran pada sekolah taman kanak-kanak (TK); kedua, jenis media pengajaran audio-visual dikembangkan dengan menggunakan model R&D oleh Sugiyono dan pengembangan media berdasarkan kriteria media pengajaran yang bagus oleh Susilana & Riyana (2007); ketiga, kualitas jenis media pengajaran yang dikembangkan adalah media pengajaran yang berkualitas sangat bagus untuk mengajar mata kuliah microteaching untuk mahaiswa S-1 Program-studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Pendidikan Ganesha Singaraja: PowerPoint memperoleh 93.02 % (kualitas sangat bagus), video pengajaran pada sekolah menengah pertama (SMP) memperoleh 94.13% (kualitas sangat bagus), dan video pengajaran pada sekolah taman kanak-kanak (TK) memperoleh 95.50% (kualitas sangat bagus). Kata Kunci : microteaching, audio-visual, media, PowerPoint, video This study aimed at: 1) identifying the types of audio-visual teaching media needed to be developed for teaching microteaching subject; 2) developing the types of audio-visual teaching media for teaching microteaching subject; 3) investigating the quality of the types of audio-visual teaching media that are developed for teaching microteaching subject for S-1 students of English Education Department Language and Art Faculty Ganesha University of Education Singaraja. The study employed R&D model proposed by Sugiyono (2010). The data were collected by using two instruments: notes and questionnaires, and were analyzed by using descriptive qualitative and quantitative analysis. The results reveal that: first, two types of audio-visual teaching media were developed for teaching microteaching; PowerPoint was used for teaching concepts and video was used for teaching learning model, two videos were developed: teaching at junior high school video and teaching at kindergarten video; second, the types of audio-visual teaching media were developed by using R&D model proposed by Sugiyono and the development of the media was based on the criteria of good teaching media proposed by Susilana & Riyana (2007); third, the qualities of the types of audio-visual teaching media were excellent qualities teaching media for teaching microteaching subject for S-1 students of English Education Department language and Art Faculty Ganesha University of Education Singaraja: the PowerPoint obtained 93.02 % (excellent quality), the Teaching at Junior High School video obtained 94.13% (excellent quality), and the Teaching at Kindergarten video obtained 95.50% (excellent quality). keyword : microteaching, audio-visual, media, PowerPoint, video